PENGARUH AMONIASI DENGAN LEVEL UREA YANG BERBEDA PADA LIMBAH KULIT SINGKONG TERHADAP KUALITAS FISIK DAN ORGANOLEPTIK - Adinda Widi Saputri; Farida Fathul; Liman Liman; Rudy Sutrisna (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the effect and optimal levels of urea in ammoniated cassava peel waste on color, aroma, texture, presence or absence of mold, pH, and temperature. This research was conducted on April 6—28th 2021 at the Nutrition and Animal Feed Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The experimental design used was a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments were cassava peel waste (P0), cassava peel waste with the addition of 1.5% urea (P1), cassava peel waste with the addition of 3% urea (P2), and cassava peel waste with the addition of 4.5% urea (P3 ). The data obtained were analysed using analysis of variance and continued with the Orthogonal Polynomial test. The result of the analysis of variance showed that the urea levels were significantly different in terms of color, scent, fungus, and pH, while texture and temperature were not significantly different. The results of the study on ammoniation of cassava peel waste with the optimal level of urea for color was 3.6%/kg dry matter of cassava peel waste, the optimal urea level for scent variable was 3.44%/kg dry matter cassava peel waste, the optimal urea level for fungus variable was 7.51%/kg dry matter cassava peel waste, and the optimal urea level for pH variable was 4.67%/kg dry matter of cassava peel waste. Keywords: ammoniation, cassava peel, color, aroma, texture, presence or absence of fungus, pH, and temperature